2004
DOI: 10.1093/toxsci/kfh110
|View full text |Cite
|
Sign up to set email alerts
|

Progression of Lung Inflammation and Damage in Rats After Cessation of Silica Inhalation

Abstract: Human epidemiologic studies have found that silicosis may develop or progress even after occupational exposure has ended, suggesting that there is a threshold lung burden above which silica-induced pulmonary disease progresses without further exposure. We previously described the time course of rat pulmonary responses to silica inhalation as biphasic, the initial phase characterized by increased but controlled pulmonary inflammation and damage. However, after a threshold lung burden was exceeded, rapid progres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
107
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(119 citation statements)
references
References 33 publications
12
107
0
Order By: Relevance
“…Silica exposure results in the induction of inflammation (Chen et al, 1999b;Fubini and Hubbard, 2003;Porter et al, 2004), and a definite role for inflammation in many of the toxic effects of silica has been demonstrated Porter et al, 2002). Induction of pulmonary inflammation, as evidenced from a significant increase in the number of AMs and PMNs as well as the activities of pro-inflammatory cytokines, MCP1 and MIP-2, was noticed in the rat lung tissue samples which were used in the current study to determine gene expression profile by microarray analysis (Sellamuthu et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Silica exposure results in the induction of inflammation (Chen et al, 1999b;Fubini and Hubbard, 2003;Porter et al, 2004), and a definite role for inflammation in many of the toxic effects of silica has been demonstrated Porter et al, 2002). Induction of pulmonary inflammation, as evidenced from a significant increase in the number of AMs and PMNs as well as the activities of pro-inflammatory cytokines, MCP1 and MIP-2, was noticed in the rat lung tissue samples which were used in the current study to determine gene expression profile by microarray analysis (Sellamuthu et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that nodular changes in the interstitium, lipoproteinosis and fibrosis are induced by intratracheal instillation of α -quartz to rats at higher dose levels than 1 mg 15,35) or by repeated inhalation exposure of rats to α -quartz at 15 mg/m 3 for 60 d 36) . However, no such lesions except fibrosis with alveolar wall thickening were found to occur in the lung of 160 m g quartz-dosed rats.…”
Section: Discussionmentioning
confidence: 99%
“…Sacrifice was at the end of exposure and after 36 days' recovery. Pulmonary inflammation and PAP increased during the recovery period in rats exposed for 40 and 60 days but not 20 days; fibrosis developed even when exposure was stopped prior to its initial development (Porter et al 2004). Several inhalation studies in rats with various quartz molecules, and with exposure from 5 days to 13 weeks (Absher et al 1989;Arts et al 2007;Baggs, Ferin, and Oberdörster 1997;Driscoll et al 1991;Henderson et al 1995;Vallyathan et al 1995), one 4-week inhalation study in mice (Velan, Kumar, and Cohen 1993), and the 11-week study in guinea pigs mentioned above (Heppleston 1986) did not demonstrate PAP but showed inflammation and fibrosis.…”
Section: Silicon Dioxide/silica/quartzmentioning
confidence: 99%